IMPORTANT ISSUES OF THE DEVELOPMENT OF E- GOVERNMENT IN THE CONDITIONS OF THE DIGITAL ECONOMY - Saidaxmedovich, Gulyamov Saidaxror; Boltaevna, Shakirova Farog’at (The journal of contemporary issues in business and government, 2021)
In this article, digitization, electronic government and its problems and solutions as a logical continuation of innovation development are covered in detail. Also, a number of proposals and recommendations have been developed within the framework of the topic.